An Efficient Strategy Combining Immunoassays and Molecular Identification for the Investigation of Fusarium Infections in Ear Rot of Maize in Guizhou Province, China - Shang, Guofu; Li, Shuqin; Yu, Huan; Yang, Jie; Li, Shimei; Yu, Yanqin; Wang, Jianman; Wang, Yun; Zeng, Zhu; Zhang, Jingbo; Hu, Zuquan (Frontiers in Microbiology, 2022)
immunoassays and molecular identification. Immunoassay based on single-chain vairable fragment (scFv) and alkaline phosphatase (AP) fusion protein was first employed to analyze these samples. Fusarium pathogens were isolated and purified from Fusarium-infected samples. Molecular identification was performed using the partial internal transcribed spacer (ITS) and translation elongation factor 1α (TEF-1α) sequences. Specific primers were used to detect toxigenic chemotypes, and verification was performed by liquid chromatography tandem mass spectrometry (LC–MS/MS). One-hundred and sixty three samples were characterized to be positive, and the infection rate was 93.14%. Sixteen species of Fusarium belonging to six species complexes were detected and F. meridionale belonging to the F. graminearum species complex (FGSC) was the dominant species. PCR identification illustrated that sixty-nine isolates (56.10%) were potential mycotoxin-producing Fusarium pathogens. The key synthetic genes of NIV, NIV+ZEN, DON+ZEN and FBs were detected in 3, 35, 7 and 24 isolates, respectively. A total of 86.11% of F. meridionale isolates carried both NIV- and ZEN-specific segments, while F. verticillioides isolates mainly represented FBs chemotype. All the isolates carrying DON-producing fragments were FGSC. These results showed that there are different degrees of Fusarium infections in Guizhou Province and their species and toxigenic genotypes display regional distribution patterns. Therefore, scFv-AP fusion-based immunoassays could be conducted to efficiently investigate Fusaium infections and more attention and measures should be taken for mycotoxin contamination in this region.